PEMANFAATAN SAMPAH TERPADU BERBASIS ECOBRICK DAN PENINGKATAN SDM PENGOLAHAN SAMPAH DI KAWASAN TOGA WARNA-WARNI - Rahmat Bangun Giarto; Masrul Huda; Mohamad Isram M. Ain; Ali Arifin Soeparlan (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
The population growth that has been increasing in Balikpapan since the impact of the development of the National Capital City (IKN), will increase waste production. Waste that is not recycled will end up in the landfill and cause pollution to the environment. Handling waste by processing waste into goods or works that can be reused is one of alternatives to reduce environmental pollution. Toga Warna-Warni is one of the PKK groups in Sungai Nangka sub-district, Balikpapan, applying 3R (Reduce, Reuse and Recycle) method in waste processing, but in fact the area faces lack facilities. The lack of waste processing facilities, waste sorting and waste banks makes the waste processing process becoming not optimal. In addition, the residents at Toga Warna-Warni have lack knowledge about the use of waste into ready-to-sell works. Therefore, to make waste management can be managed properly and sustainably, mentoring and human resource development both in terms of waste reduction and how to handle (utilization), preparation to become a model place for waste management through Community Service is very necessary. By having this program, environmental pollution caused by the waste can be reduced and the community’s economy can increase because it can sell the results of processing waste into goods having economic value. In addition, the idea of Toga Warna Warni becoming a model in Balikpapan City in waste management and education media to Balikpapan people will be realized.